Unintended pregnancy among older married women of reproductive age in a city in Southwest Nigeria: A household-based study - Aanuoluwapo Adeyimika Afolabi; Ayo Stephen Adebowale; Tosin Olajide Oni; Akanni Ibukun Akinyemi (Advances in Medicine, Psychology, and Public Health)
Introduction: Unintended pregnancies constitute one of the major public health problems of important concern in Nigeria, where sex refusal in marriage might be impossible. This descriptive, household-based study, investigated the prevalence and predictors of unintended pregnancy in the past two years among married women aged 35-49 years in Ibadan, South West, Nigeria. Methods: A three-stage sampling technique was used to recruit 425 respondents across three local government areas. Data were collected and analyzed using a structured interviewer-administered questionnaire. The dependent variable, “Unintended pregnancy,” was defined as an unplanned, unwanted, or mistimed pregnancy. Data were summarized using descriptive statistics. Bivariate chi-square tests were used to determine the factors associated with unintended pregnancy, while binary logistic regression was used to determine the predictors of unintended pregnancy (α0.05). Results: The mean age of the women was 41.1 ± 4.2 years, 149 (35.1%) had high autonomy, while 233 (54.8%) had medium autonomy. Further, 177 (41.6%) were poor, while 106 (25.0%) were rich. In all, 108 (25.4%) women have had an unintended pregnancy. Women with low autonomy (AOR=3.41, 95%C.I.=1.70-6.82, p=0.001) and medium autonomy (AOR=2.41, C.I.=1.29-4.49, p=0.006) had higher odds of unintended pregnancy. The likelihood of unintended pregnancy was higher among women living in poor households (AOR=2.04, 95%C.I.=1.13-3.68, p=0.017). Conclusions: The level of unintended pregnancy was high among older women of reproductive age in Ibadan. Social interventions that focus on empowerment of such women should be undertaken by governmental agencies, non-governmental agencies, and community-based organizations to increase women’s autonomy and reduce unintended pregnancy among them.